Pengaruh Perencanaan Pajak, Penghindaran Pajak, dan Prudence Accounting terhadap Nilai Perusahaan pada Perusahaan Asuransi - Palupi, Amalia; Susilowati, Lantip (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This study aims to: (1) examine the simultaneous significant effect of tax planning, tax avoidance, and prudence accounting on the value of insurance companies; (2) analyze the partial significant effect of tax planning on the value of insurance companies; (3) assess the partial significant effect of tax avoidance on the value of insurance companies; and (4) investigate the partial significant effect of prudence accounting on the value of insurance companies. This research employs a quantitative approach with an associative research design. The sample is selected using a purposive sampling technique. Secondary data is obtained from the official website of the Indonesia Stock Exchange (IDX). The study utilizes panel data regression analysis, conducted using EViews 12 software. The findings indicate that: (1) tax planning, tax avoidance, and prudence accounting collectively have a significant positive effect on the value of insurance companies; (2) tax planning, when examined individually, does not have a significant effect on the value of insurance companies; (3) tax avoidance, when considered separately, has a significant positive effect on the value of insurance companies; and (4) prudence accounting, when analyzed in isolation, has a significant negative effect on the value of insurance companies.